Mid-Libertarianism: A Critique - Block, Walter E. Block (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
Mid-libertarianism is the new kid on the libertarian block. Torpman (2021) is critical of what he calls “classical libertarianism” and attempts to improve it with the introduction of his new perspective, “mid-libertarianism.” The present paper maintains that the good, old-time philosophy of plain libertarianism is invulnerable to his criticisms of it, that his “mid-libertarianism” has problems of its own, and thus there is no reason to substitute the one for the other.